2010
DOI: 10.1038/jid.2010.292
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Increase in Skin Inflammation in the Absence of CCR4

Abstract: The chemokine receptors are seven transmembrane, G-protein-coupled surface receptors that play key roles in the migration and localization of leukocytes to the skin during physiologic and inflammatory states. Their ligands, chemokines, are small secreted proteins that initiate leukocyte chemoattraction. Recent data indicate that known subsets of T helper (Th) cells express signature chemokine receptors (e.g., CXCR3, CCR3/4, and CCR6) that help to define individual subsets such as Th1, Th2, and Th17 cells, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…19 On detection of a pathogen, keratinocytes undergo accelerated growth and differentiation, which result in a marked increase in the synthesis of antimicrobial proteins, chemokines, and cytokines that rapidly recruit and activate specific T-cell subsets responsible for orchestrating protective immunity. 20 This response is organism specific: extracellular bacterial or fungal infections trigger IL-17, CCL20, CXCL9, or CXCL10 synthesis to elicit T H 17 cells 20,21 or T H 1 influx and activation 22 ; helminth infection activates thymic stromal lymphopoietin, IL-25, IL-33, CCL17, or CCL22 synthesis to direct T H 2 responses 13,[23][24][25] ; intracellular bacteria, protozoa, and viruses induce type I immune responses (IL-12, IL-15, and IFN-g) 26,27 ; and gram-negative bacteria can trigger increased production of TNF, IL-1, and other cytokines that drive increased synthesis of CXCL1, CXCL2, CXCL3, CXCL5, and CXCL8 that encourage neutrophil chemotaxis into infected sites. 28,29 (Table I).…”
Section: Immune Mechanisms In Activated Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…19 On detection of a pathogen, keratinocytes undergo accelerated growth and differentiation, which result in a marked increase in the synthesis of antimicrobial proteins, chemokines, and cytokines that rapidly recruit and activate specific T-cell subsets responsible for orchestrating protective immunity. 20 This response is organism specific: extracellular bacterial or fungal infections trigger IL-17, CCL20, CXCL9, or CXCL10 synthesis to elicit T H 17 cells 20,21 or T H 1 influx and activation 22 ; helminth infection activates thymic stromal lymphopoietin, IL-25, IL-33, CCL17, or CCL22 synthesis to direct T H 2 responses 13,[23][24][25] ; intracellular bacteria, protozoa, and viruses induce type I immune responses (IL-12, IL-15, and IFN-g) 26,27 ; and gram-negative bacteria can trigger increased production of TNF, IL-1, and other cytokines that drive increased synthesis of CXCL1, CXCL2, CXCL3, CXCL5, and CXCL8 that encourage neutrophil chemotaxis into infected sites. 28,29 (Table I).…”
Section: Immune Mechanisms In Activated Skinmentioning
confidence: 99%
“…5,9 In normal, noninflamed skin Treg cells are characterized by expression of cutaneous lymphocyteassociated antigen (a skin-homing receptor), 94 by the costimulatory molecule CD28, 95 and by expression of chemokine receptors for CCL27/28 (CCR10), 94,96 CCL20 (CCR6), 97 and CCL17/22 (CCR4). 24 They secrete high levels of cytokines that suppress inflammatory responses, including IL-10, IL-35, and TGF-b (as discussed in section 4). 98,99 Most Treg cells express the high-affinity IL-2 receptor (CD25) and the transcription factor forkhead box P3 (Foxp3), which plays a role in their development and function (maintenance of suppressive role and self-tolerance).…”
Section: Treg Cellsmentioning
confidence: 99%
“…However, expression of CCR6 mRNA was not influenced by injection of either CpG‐DNA‐stimulated LDCs or histamine‐stimulated LDCs. It has been reported that CXCR3 and CCR6 are expressed on the surface of Th1 and Th17 cells, respectively . Also, it is known that CCR4 is expressed on the surface of both of Th2 and T reg cells .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CXCR3 and CCR6 are expressed on the surface of Th1 and Th17 cells, respectively . Also, it is known that CCR4 is expressed on the surface of both of Th2 and T reg cells . Therefore, comparison of cytokine patterns and detection of the expression of these chemokine receptors in lymph nodes would predict the development of each T cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CCR4 + T cells have been identified in inflammatory conditions affecting the synovium (Leipe et al, 2010), lung (Panina-Bordignon et al, 2001; Nouri-Aria et al, 2002; Vijayanand et al, 2010), liver (Oo et al, 2010), peritoneum and appendix (Michelle L. McCully and Bernhard Moser, unpublished observations), indicating that CCR4 aids the non-selective migration of effectors to many inflamed sites. In mice, early studies implicated CCR4 as being critical for the migration of antigen-specific effector cells and Tregs to inflamed skin (Reiss et al, 2001; Campbell et al, 2007), but more recent studies found that skin inflammatory responses were intact or even elevated in the absence of CCR4 expression (Lehtimaki et al, 2010; Sells and Hwang, 2010) underlining the significant amount of redundancy in the chemokine network during inflammation.…”
Section: Chemokines Present In Human Skinmentioning
confidence: 99%